ETIKA PUBLIK SEBAGAI RUANG DIALOG AGAMA (Genealogi Civil Religion Dalam Keberagamaan NU) - Chafid Wahyudi (Jurnal Hikmatuna, 2015)
The existence of different faiths in one country, where each offers life norms, prevents the use of one religion as the sole general source for reference. Therefore, it becomes a necessity to find one general concept incorporating all those religions. This calls for a concept of civil religion. It is a view that puts religion norms as merely having substantives function. In other words, it looks for a compromise held by all faiths to keep all parties respecting each other. This is the reason this article will discuss religious practices demonstrated by NU have shown to contain substantial elements of civil religion. This then will lead to the building of public ethics as a room for dialogue acting as substitute of religions.